HSP90 Inhibition Drives Degradation of FGFR2 Fusion Proteins: Implications for Treatment of Cholangiocarcinoma. Issue 1 (14th December 2018) - Lamberti, Dante; Cristinziano, Giulia; Porru, Manuela; Leonetti, Carlo; Egan, Jan B.; Shi, Chang‐Xin; Buglioni, Simonetta; Amoreo, Carla A.; Castellani, Loriana; Borad, Mitesh J.; Alemà, Stefano; Anastasi, Sergio; et al.
Abstract : About 15% of intrahepatic cholangiocarcinomas (ICCs) express constitutively active fibroblast growth factor receptor 2 (FGFR2) fusion proteins (FFs) generated by chromosomal translocations. FFs have been nominated as oncogenic drivers because administration of FGFR tyrosine kinase inhibitors (F‐TKIs) can elicit meaningful objective clinical responses in patients carrying FF‐positive ICC. Thus, optimization of FF targeting is a pressing clinical need. Herein, we report that three different FFs, previously isolated from ICC samples, are heat shock protein 90 (HSP90) clients and undergo rapid degradation upon HSP90 pharmacological blockade by the clinically advanced HSP90 inhibitor ganetespib. Combining catalytic suppression by the F‐TKI BGJ398 with HSP90 blockade by ganetespib suppressed FGFR2‐TACC3 (transforming acidic coiled‐coil containing protein 3) signaling in cultured cells more effectively than either BGJ398 or ganetespib in isolation. The BGJ398 + ganetespib combo was also superior to single agents when tested in mice carrying subcutaneous tumors generated by transplantation of FGFR2‐TACC3 NIH3T3 transformants. Of note, FF mutants known to enforce clinical resistance to BGJ398 in ICC patients retained full sensitivity to ganetespib in cultured cells. Conclusion: Our data provide a proof of principle that upfront treatment with the BGJ398 + ganetespib combo improves therapeutic targeting of FGFR2 fusions in an experimental setting, which may be relevant to precision medicine approaches to FF‐driven ICC.